Business Development Strategies for Stalls and Economic Impact Through Menu Innovation and Digital Promotion - Arief Rahman; Reni; Elmi Nurvianti; Neni Nuraini (Journal of Economic Education and Entrepreneurship Studies, 2024)
Conditions that can be controlled by Warung Zipau based on internal strategies by referring to the IFAS (Internal Factor Analysis Summary) table obtained a value of (3.31), this shows that the strength score is greater than the weakness score. Meanwhile, the external strategy in the EFAS (External Factor Analysis Summary) table obtained a value of (3.31), this shows that the opportunity value score is more than the threat value score. Reviewing the calculation results in the IFAS and EFAS tables shows that the results of the SO strategy are in quadrant I, where this position supports an aggressive strategy, meaning that this position is a very profitable situation because Warung Zipau has quite strong strength. Achieve business goals, the zipau stall business must develop strategies in the future by implementing a Growth Oriented Strategy, namely by expanding, developing varied menu choices and developing promotions using social media because the opportunities in this media are very large. wide open and reaches many groups.